A Novel and Comprehensive Wellness Assessment for Lifestyle‐Based Interventions - Katie M. Ellison; Kimberly A. Smith; José R. Fernández; Eric P. Plaisance; Tsz Kiu Chui; James O. Hill; Holly R. Wyatt; R. Drew Sayer (Obesity Science & Practice)
ABSTRACT Objective While weight status and clinical laboratory measures are important in assessing obesity‐related disease severity and chronic disease risk, including a broader range of emotional, psychosocial, and behavioral factors would provide greater context of an individual's overall state of wellness and could be used to better guide treatment decisions. The purpose of this research was to develop a comprehensive Lifestyle Wellness assessment for use in lifestyle‐based wellness interventions and programs. Methods A cross‐sectional exploratory factor analysis (EFA) was conducted using baseline data from N = 138 adults participating in behavioral weight loss trials. An unweighted least squares extraction method with oblique rotation was used. Twenty‐one putative measures spanning constructs related to metabolic health, emotional health/wellbeing, body weight and composition, diet quality, and fitness were analyzed for retention. Results Mean body mass index (BMI) was 38.0 ± 6.6 kg/m2, mean age was 57.3 ± 11.1 years, and 77.5% of participants were female. The EFA produced a five‐factor model with 13 items that explained 80.3% of the variance. The retained factors included: (1) Psychosocial State: mindfulness, resilience, quality of life, and happiness; (2) Blood Pressure State: systolic and diastolic blood pressure; (3) Lipid State: total cholesterol and LDL‐cholesterol; (4) Fitness State: grip strength, jump height, and percent body fat; and (5) Body State: BMI and waist circumference. Conclusions Lifestyle Wellness is a comprehensive assessment that enables innovative wellness‐related research such as metabolically healthy obese phenotypes and weight‐neutral interventions. Future research should include investigations in additional populations with greater age, sex/gender, and body size diversity.